Studies on the Singapore economy - Choy, Keen-Meng (World Scientific Pub., 2012)
Though there are several book on the Singapore economy, none have focused on the time series-based investigations. This book tries to address that gap and attempts to add to what we know from studies in the descriptive tradition.